Inoperable or incompletely resected craniofacial osteosarcoma treated by particle radiotherapy - Seidensaal, Katharina; Dostal, Matthias; Liermann, Jakob; Adeberg, Sebastian; Weykamp, Fabian; Schmid, Maximillian P.; Freudlsperger, Christian; Hoffmann, Jürgen; Hompland, Ivar; Herfarth, Klaus; Debus, Jürgen; Harrabi, Semi B. (Frontiers in Oncology, 2022)
Background: To report survival of craniofacial osteosarcoma patients treated by particle radiotherapy. Methods: Between January 2010 until December 2021, 51 patients with primary (N=35) or recurrent (N=16) inoperable or incompletely resected craniofacial osteosarcoma were treated. In most cases intracranial infiltration (59%) and macroscopic tumor on MRI/ CT (75%) were present. Thirteen had a secondary osteosarcoma (25%). Treatment concepts included combined ion beam radiotherapy (CIBRT, N=18), protons only (N=3), carbon ions only (N=12), IMRT with a carbon ion boost (N=5) and carbon ion re-irradiation (N=13). Eighty percent (N=41) received additionally chemotherapy, most frequently EURAMOS-1 (47%) or EURO-B.O.S.S. (18%). Results: The median age was 38, all patients finished treatment predominantly as outpatients (N=44). Information on overall survival was available for N=49 patients. The median follow-up of the survivors was 55 months. For the whole cohort 1y, 2y, 3y and 5y overall survival (OS) was 82.8%, 60.4%, 55.2% and 51.7%, respectively. Those treated by CIBRT (N=17) demonstrated a superior OS with 92.9% after 1y and 2y and 83.6% after 3y and 5y. The median clinical target volume (CTV) was 192.7 cc and 95.2 cc for the primary and boost plan, respectively. CIBRT, primary diagnosis, age ≤ 40a and no macroscopic residual tumor were associated with improved survival in univariate analysis (p=0.006, p=0.004, p=0.002, p=0.026, respectively), while any foregoing resection compared to biopsy was not identified as a prognostic factor. CIBRT and no macroscopic residual tumor were confirmed as independent predictors of OS on multivariate analysis (HR=0.107, 95% CI =[0.014, 0.797], p=0.029 and HR=0.130, 95% CI =[0.023, 0.724], p=0.020, respectively). No acute toxicity > grade III was observed. Conclusion: CIBRT shows promising results for patients with inoperable or incompletely resected craniofacial osteosarcoma.